Simultaneous Determination of Fluoxetine, Estrone, Pesticides, and Endocrine Disruptors in Wastewater by Gas Chromatography-Mass Spectrometry (GC-MS) Following Switchable Solvent-Liquid Phase Microextraction (SS-LPME) - Erarpat, Sezin; Caglak, Abdulkadir; Bodur, Suleyman; Chormey, Selali Dotse; Engin, Guleda Onkal; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2019)
A simple and sensitive analytical method for the determination of fluoxetine, estrone and selected pesticides and endocrine disruptors has been proposed for wastewater analysis by gas chromatography-mass spectrometry (GC-MS). A switchable solvent was produced with N,N-dimethylbenzylamine by changing its hydrophobic properties by the addition of CO2 for protonation. Sodium hydroxide was added to switch the solubility of the extraction solvent and to allow phase separation in the sample/standard medium. Analytical parameters affecting the extraction outputs such as volume of switchable solvent, concentration and volume of sodium hydroxide, mixing type and period were investigated to improve the extraction recovery of the selected analytes. Under the optimum conditions, limits of detection and limits of quantification for the analytes were calculated in the ranges of 0.16-8.6 ng mL(-1) and 0.54-29 ng mL(-1), respectively. The developed method was successfully applied to synthetic wastewater and two municipal wastewater samples. None of the selected analytes were detected in the samples. High recovery values demonstrated that the proposed method was reliable and applicable to complex matrices.
Keywords: Endocrine disruptors; estrone; fluoxetine; gas chromatography-mass spectrometry (GC-MS); pesticides; switchable solvent-liquid liquid microextraction (SS-LPME); OPTIMIZATION; Chemistry